The model influence of authoritarian parenting, extraversion personality, and conformity to bullying among students - Pipih Muhopilah; Fatwa Tentama; Yuzarion Yuzarion (Institute of Advanced Engineering and Science, 2021)
The purpose of this study was to analyze the model of the influence of authoritarian parenting, extraversion personality, and conformity to bullying in students. The population in this study were all students of grade eight of X, Y, Z state middle school in Yogyakarta, consisting of 524 students. The sample in this study was 185 students. The sampling technique used in this study was cluster random sampling. The data were collected with the scales which were developed for each variable studied. Data analysis was performed by testing the outer and inner models using structural equation model (SEM) through the Smart Partial Least Square 3.2.8 program. The results of this study were the formation of the model of the influence of authoritarian parenting, extraversion personality, and conformity to bullying that was found to be fit with empirical data. Overall, the findings suggested that all variables under investigation (authoritarian parenting, extraversion personality, and conformity) had positive and a very significant influence on bullying. This model can be used as a valid reference in developing bullying variables.